Customer's level of satisfaction towards counter service: A study at TM Point / Edward Liding John - John, Edward Liding (2007)
Telekom Sales & Services Sdn. Bhd. (TM Sales & Services ) is a customer service organization which provides a one-stop solution for TM Group products and services. With the Vision, " To be a one-stop centre for TM Group products and services" and as a wholly-owned subsidiary of TM, TM Sales & Services is determine to provide excellent services for TM Group's customers and to offer competitive ICT products and services. Currently, Telekom Sales & Services Sdn. Bhd. has more than 100 ISO Certified TM point outlets nationwide. These TM point outlets serve as the primary channels in providing TM's services such as service provisioning, bill payments, fixed line, multimedia and other value added services. TM Sales & Services also markets a wide range of telecommunications as well as IT related products and accessories.